Validación de la presencia de Tillandsia chlorophylla L. B. Sm. (Bromeliaceae) para Honduras - Morales-Molina, Sobeida (2024)
After doing the exhaustive review of reported records of Tillandsia chlorphylla L. B. Sm. In Honduras, the species is confirmed from a population found in the west of the country, increasing the number of bromeliad species recorded in the territory to 138. As a result of the threats that exist in the area where the species was reported, it is recommended to implement protection measures for this recently found population, as well as more severe reviews for the other species of bromeliads, since in this locality, being on the border, it can be report an increase in new registrations for Honduras.